Synchronization by Daytime Restricted Food Access Modulates the Presence and Subcellular Distribution of β-Catenin and Its Phosphorylated Forms in the Rat Liver - De Ita-Pérez, Dalia Luz; Díaz-Muñoz, Mauricio (Frontiers in Endocrinology, 2017)
β-catenin, the principal effector of the Wnt pathway, is also one of the cadherin cell adhesion molecules; therefore, it fulfills signaling and structural roles in most of the tissues and organs. It has been reported that β-catenin in the liver regulates metabolic responses such as gluconeogenesis, and histological changes in response to obesity-promoting diets. The function and cellular location of β-catenin is finely modulated by coordinated sequences of phosphorylation-dephosphorylation events. In this paper we evaluated the levels and cellular localization of liver β-catenin variants; more specifically β-catenin phosphorylated in serine 33 (this phosphorylation provides recognizing sites for β-TrCP, that results in ubiquitination and posterior proteasomal degradation of β-catenin), and β-catenin phosphorylated in serine 675 (phosphorylation that enhances signaling and transcriptional activity of β-catenin through recruitment of different transcriptional coactivators). β-catenin phosphorylated in serine 33 in the nucleus shows day-night fluctuations in their expression level in the Ad Libitum group. In addition, we used a daytime restricted feeding (DRF) protocol to show that the above effects are sensitive to food access-dependent circadian synchronization. We found through western blot and immunohistochemical analyses that DRF protocol promoted 1) higher total β-catenins levels mainly associated with the plasma membrane, 2) reduced the presence of cytoplasmic β-catenin phosphorylated in serine 33, 3) an increase in nuclear β-catenin phosphorylated in serine 675, 4) differential co-localization of total β-catenins/β-catenin phosphorylated in serine 33 and total β-catenins/β-catenin phosphorylated in serine 675 at different temporal points along day and in fasting and refeeding conditions, and 5) differential liver zonation of β-catenin variants studied along hepatic acinus. In conclusion, the present data comprehensively characterizes the effect food synchronization has on the presence, subcellular distribution, and liver zonation of β-catenin variants. These results are relevant to understand the set of metabolic and structural liver adaptations that are associated with the expression of the food entrained oscillator.